2022
DOI: 10.21203/rs.3.rs-1627487/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-normal versus low-normal mean arterial pressure thresholds in critically ill patients: A systematic review and meta-analysis of randomized trials

Abstract: Targeted blood pressure thresholds remain unclear in critically ill patients. Two prior systematic reviews have not demonstrated differences in mortality with a high mean arterial pressure (MAP) threshold but they only included patients with septic shock. Thus, we conducted an updated systematic review and meta-analysis of randomized controlled trials (RCTs) that compared the effect of a high-normal versus low-normal MAP on mortality in all pertinent disease states for critically ill patients. We searched six… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Authors have previously suggested that MAP augmentation may be an effective treatment strategy in the post-resuscitation setting [ 38 , 40 ]. However, the neutral results of randomised control trials investigating MAP augmentation [ 7 9 , 14 ], and lack of influence of MAP augmentation on neurologic outcome demonstrated in a recent meta-analysis [ 41 ], have led investigators to call into question the effectiveness of such an approach. Such discordance between the perceived importance of augmenting MAP and the lack of benefit for neurologic outcome demonstrated in clinical trials may be explained by dysfunction in the latter stages of the oxygen cascade (see Stage 2: oxygen diffusion & Stage 3: oxygen utilisation ) and by individualised perfusion thresholds that may reflect patient-specific cerebrovascular physiology [ 42 ].…”
Section: Stage 1: Convective Oxygen Deliverymentioning
confidence: 99%
“…Authors have previously suggested that MAP augmentation may be an effective treatment strategy in the post-resuscitation setting [ 38 , 40 ]. However, the neutral results of randomised control trials investigating MAP augmentation [ 7 9 , 14 ], and lack of influence of MAP augmentation on neurologic outcome demonstrated in a recent meta-analysis [ 41 ], have led investigators to call into question the effectiveness of such an approach. Such discordance between the perceived importance of augmenting MAP and the lack of benefit for neurologic outcome demonstrated in clinical trials may be explained by dysfunction in the latter stages of the oxygen cascade (see Stage 2: oxygen diffusion & Stage 3: oxygen utilisation ) and by individualised perfusion thresholds that may reflect patient-specific cerebrovascular physiology [ 42 ].…”
Section: Stage 1: Convective Oxygen Deliverymentioning
confidence: 99%